Inheritance as a form of access to land and the situation of women in the southwest of Buenos Aires (Huellas, 2024)
Inheritance is the main form of access to land for family farming (FF) in the southwest (SO) region in Buenos Aires province, with a clear preference towards men when inheriting. Although there are no regulatory hindrances for women to have access to land in the Argentine legal system, they face socio-cultural obstacles to inheriting land. For this reason, the present work aims at analysing, from a qualitative approach and with semi-structured interviews as the main data collection technique, the situation and limitations regarding access to land for women in the Buenos Aires SO region. The incorporation of the gender perspective in the analysis of the problem of access to land faced by producer families in the Buenos Aires SO region shows that women from family farmers face various structural and historical inequalities due to their condition of being women, where the land becomes crucial since it brings together both the productive unit and the family home.
Keywords: land; access; women; family farming